A Legal Analysis of the Influence of International Trade on Import Restriction Policies in Indonesia - Wiwik Sri Widiarty; Jihyun Park; Tria Sasangka Putra (Jurnal Hukum, 2025)
This study examines how international trade dynamics influence Indonesia’s import restriction policies, focusing on the Minister of Trade Regulation Number 36/2023 and its amendment, the Minister of Trade Regulation Number 8/2024. The research aims to analyze how global trade commitments, particularly WTO principles such as GATT Articles I and XI, shape Indonesia’s regulatory framework; assess the economic and practical consequences of these restrictions for domestic industries and supply chains; and evaluate the balance between protectionism and trade liberalization, highlighting long-term implications for competitiveness and sovereignty. Using a normative juridical approach, the study reviews primary, secondary, and tertiary legal materials, including national legislation and international conventions such as WTO/GATT, AFTA, NAFTA, and ACFTA. Legal analysis is conducted qualitatively, focusing on trade regulations, licensing measures, and policy adaptations, complemented by doctrinal interpretation to construct a comprehensive understanding of the legal framework. Findings reveal that while the Minister of Trade Regulation Number 36/2023 sought to protect domestic industries and consumers, it disrupted supply chains and delayed shipments, imposing economic costs. Subsequent relaxations under the Minister of Trade Regulation Number 8/2024 and later reforms in 2025 improved efficiency and balanced deregulation with strategic safeguards. The study underscores the trade-off between short-term protectionism and long-term competitiveness, emphasizing the need for adaptive, transparent, and WTO-compliant policies. Insights from this research provide guidance for strengthening Indonesia’s import regulations while maintaining compliance with international trade obligations.